Teaching in the “New Normal”: Thoughts and Experiences of Teachers on the Shape of the Academe - Alexis Arizabal Enriquez (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2022)
At the start of the year, the world was thrown into disarray by a pandemic. The first months of 2020 the COVID-19 or Corona Virus, which originally appeared in China last December 2019, quickly traveled to the Philippines. Locally it had its first case on March 7, 2020. While learning must continue throughout the epidemic, a mindset shift is required for an effective distant learning experience. Lecturers are gradually adapting to remote instruction, some aspects of teaching and learning cannot be recreated at home. This qualitative- descriptive research focused on thoughts and experiences of 16 teachers as they try to reorder and reorganize themselves in the academe. Constrained by the pandemic, responses were collected using the google form and themed accordingly. It used the Thematic Analysis of Braun and Clarke (2006) as a method in analysing the data. The teachers revealed empowerment, trustworthiness of officials, negation, readiness, hopefulness, time management, elusiveness, flexibility, and security shaped them in several aspects amidst this pandemic while realizing the importance of serving students with quality. Administrators, government officials, and others must evaluate how schools might recover faster, with a transformed sense of duty, a deeper knowledge and firmness of the need to bridge the gap in opportunities and ensuring that all kids have equal possibilities for a quality education. The call to exceptional service is a lifetime goal for them, and as academic frontliners with the ability to respond to pandemic issues, they must also ensure optimum safety.